Analisis Hukum Pernikahan Turun Ranjang dalam Perspektif Hukum Islam - Ameytia Rizka Aulia; Benediktus Josua Gea; Despri Mariyani Siahaan; Olivia Hana Putri Nababan; Syuratty Astuti Rahayu Manalu (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
The “turun ranjang” marriage is a traditional practice found in several Indonesian ethnic groups, in which a man marries the younger sister of his deceased or divorced wife. This tradition aims to maintain family harmony, protect children, and preserve kinship ties. From the perspective of Islamic law, such a marriage is permissible as long as it fulfills the legal requirements and pillars of marriage, including the presence of a guardian, witnesses, mutual consent, and the absence of coercion. However, if any of these conditions are not met, the marriage may be considered invalid according to Islamic law. While this tradition has positive aspects such as preventing adultery and preserving family unity it may also lead to social conflict when performed under pressure or without full consent. Therefore, it is essential for those involved to seek guidance from Islamic scholars or legal experts to ensure the marriage aligns with religious principles and promotes family harmony. Overall, the “turun ranjang” marriage can be accepted if conducted with sincerity, awareness, and compliance with Islamic law.